N, N‐dimethyl‐2‐phenylpropan‐1‐amine – new designer agent found in athlete urine and nutritional supplement. Issue 4 (29th October 2014) - Kwiatkowska, Dorota; Wójtowicz, Marzena; Jarek, Anna; Goebel, Catrin; Chajewska, Katarzyna; Turek‐Lepa, Ewa; Pokrywka, Andrzej; Kazlauskas, Rymantas
<x xml:space="preserve">Abstract</x> Reports of new designer agents banned in sport being detected in supplements widely available for athletes are constantly emerging. The task of anti‐doping laboratories is to control athletes for the presence of substances listed by the World Anti‐Doping Agency (WADA) and those that are structurally/biologically similar to them. Recently, a new designer stimulant, N, N‐dimethyl‐2‐phenylpropan‐1‐amine (NN‐DMPPA), was detected by the WADA accredited anti‐doping laboratory in Warsaw during routine anti‐doping control. The urine samples from four athletes were analyzed in the screening method for stimulants and narcotics and the presence of NN‐DMPPA was detected. The identity of NN‐DMPPA was confirmed by gas chromatography‐mass spectrometry using a synthesized reference standard. The measured concentrations of NN‐DMPPA were between 0.51 and 6.51 µg/mL. The presence of the NN‐DMPPA compound has been detected in the 'nutritional supplement' NOXPUMP that had been purchased in a store in Poland. NN‐DMPPA at 121.7 µg/g was indicated in the investigated supplement together with another banned stimulant β‐methylphenethylamine. The presence of this new stimulant was not indicated on the labelling of the supplement, a situation which is not unusual within this market. Thus, it is important to make athletes aware of the risk related to the use of supplements. Moreover, specific legistation dealing with the commercialization of drugs banned for sport should be undertaken. Copyright © 2014 John Wiley & Sons, Ltd.